A crystallographic study of human NONO (p54nrb): overcoming pathological problems with purification, data collection and noncrystallographic symmetry. Issue 6 (1st June 2016) - Knott, Gavin J.; Panjikar, Santosh; Thorn, Andrea; Fox, Archa H.; Conte, Maria R.; Lee, Mihwa; Bond, Charles S.
Abstract : The structure determination of the NONO homodimer is reported, detailing the challenges in protein purification and identifying and overcoming overlapping reflections. Abstract : Non‐POU domain‐containing octamer‐binding protein (NONO, a.k.a. p54 nrb ) is a central player in nuclear gene regulation with rapidly emerging medical significance. NONO is a member of the highly conserved Drosophila behaviour/human splicing (DBHS) protein family, a dynamic family of obligatory dimeric nuclear regulatory mediators. However, work with the NONO homodimer has been limited by rapid irreversible sample aggregation. Here, it is reported thatl ‐proline stabilizes purified NONO homodimers, enabling good‐quality solution small‐angle X‐ray structure determination and crystallization. NONO crystallized in the apparent space group P 21 with a unique axis ( b ) of 408.9 Å and with evidence of twinning, as indicated by the cumulative intensity distribution L statistic, suggesting the possibility of space group P 1. Structure solution by molecular replacement shows a superhelical arrangement of six NONO homodimers (or 12 in P 1) oriented parallel to the long axis, resulting in extensive noncrystallographic symmetry. Further analysis revealed that the crystal was not twinned, but the collected data suffered from highly overlapping reflections that obscured the L ‐test. Optimized data collection on a new crystal using higher energy X‐rays, a smaller beam width and an increased sample‐to‐detector distance produced non‐overlapping reflections to 2.6 Å resolution. The steps taken to analyse and overcome this series of practical difficulties and to produce a biologically informative structure are discussed.